The early design stage for building renovation with a novel loop-heat-pipe based solar thermal facade (LHP-STF) heat pump water heating system: Techno-economic analysis in three European climates. (December 2015) - Zhang, Xingxing; Shen, Jingchun; Adkins, Deborah; Yang, Tong; Tang, Llewellyn; Zhao, Xudong; He, Wei; Xu, Peng; Liu, Chenchen; Luo, Huizhong
Highlights: LHP-STF was evaluated from both technical and economic aspects for three EU climates. The impact of LHP-STF on the overall building socio-energy performance was explored. A dedicated business model was developed to study the economic feasibility of LHP-STF. Three fundamental methods for financial measurement of LHP-STF were analysed. Four investment options were considered in this business model. Abstract: Most of the building renovation plans are usually decided in the early design stage. This delicate phase contains the greatest opportunity to achieve the high energy performance buildings after refurbishment. It is therefore important to provide the pertinent energy performance information for the designers or decision-makers from multidisciplinary and comparative points of view. This paper investigates the renovation concept of a novel loop-heat-pipe based solar thermal facade (LHP-STF) installed on a reference residential building by technical evaluation and economic analysis in three typical European climates, including North Europe (represented by Stockholm), West Europe (represented by London) and South Europe (represented by Madrid). The aim of this paper is firstly to explore the LHP-STF's sensitivity with regards to the overall building socio-energy performance and secondly to study the LHP-STF's economic feasibility by developing a dedicated business model. The reference building model was derived from the U.S. Department of Energy (DOE) commercial buildings research, in which the energy data for the building models were from the ASHRAE codes and other standard practices. The financial data were collected from the European statistic institute and the cost of system was based on the manufactured prototype. Several critical financial indexes were applied to evaluate the investment feasibility of the LHP-STF system in building renovation, such as Payback Period (PP), Net Present Value (NPV), and the modified internal rate of return method (IRR). Four common investment options were considered in this business model, including buying outright (BO), buying by instalment (BI), energy efficiency funding (EEF) and power purchase agreement (PPA). The research results indicate that the LHP-STF could contribute to the hot water load throughout the year with substantially reduced heating load in winter, and yet a slight increased cooling load in summer. Among four investment options, the BO was considered as the best investment method with the highest NPV, IRR and the shortest payback period. With regards to relatively limited solar resources, London was found to be the best place for investment with the highest economical revenues and an attractive payback period of less than four years for all purchase options. Although Madrid has the richest solar resource, this system has the lowest economic profit and the longest payback period. This outcome confirms that the renewable energy incentives have a higher impact than solar resources on current solar thermal facade technologies under such pricing fundamentals. This multidisciplinary research is expected to be helpful for the strategic decisions at the early design stage for building renovation with the proposed system and further promote development of solar driven service system, leading to the savings in fossil fuel consumption and reduction in carbon emission.